High apolipoprotein M serum levels correlate with chronic obstructive pulmonary disease. Issue 1 (December 2016) - Li, Hui; Liu, Yinyin; Wang, Ling; Shen, Ting; Du, Wenhan; Liu, Zhijun; Chen, Ruohong; Hu, Min
Abstract Background Recently, variations in a component of high-density lipoprotein (HDL), namely apolipoprotein M (apoM), were found to be associated with chronic obstructive pulmonary disease (COPD). The aim of this study was to evaluate the association between apoM and COPD severity. Factors associated with apoM, COPD, or coronary artery disease (CAD) were also assessed. Methods A total of 110 COPD patients and 110 age- and sex-matched non-COPD controls were included. Among them, thirty COPD patients and seven non-COPD controls had CAD. ApoM and pentraxin-3 levels were measured by ELISA. Additionally, the levels of high-sensitivity C-reactive protein (hs-CRP), cholesterol, and triglyceride were assessed using an automatic biochemical analyzer. Results Serum apoM levels increased gradually with COPD severity, with the most prominent apoM elevation observed in very severe COPD cases. In addition, ApoM was correlated with percent-predicted forced expiratory volume in one second (% predicted FEV1) (r  = −0.38, P  < 0.001), low-density lipoprotein cholesterol (LDL-C) (r  = 0.23, P  < 0.017), and hs-CRP (r  = 0.24, P  = 0.01) in COPD patients. Furthermore, apoM was shown to be a risk factor for COPD onset (OR = 1.095, 95 % CI = 1.034–1.160, P  = 0.002), but not associated with CAD in COPD patients. Conclusions Serum apoM was elevated in COPD patients and increased gradually with COPD severity. However, there was no association between apoM and CAD development in COPD patients.